Forms of Lord Vishnu - a list - Shodhganga thesis (2022)
This list is from the thesis Iconography of hoysala period temples. Title of Thesis : Iconography of hoysala period temples Name of the Researcher : Nangia, Renupum Name of the Guide : Deo, S B Completed Year : 1985 Abstract : Abstract not available Name of the Department : Deccan College Post Graduate and Research Institute Pune Name of the University : Savitribai Phule Pune University